Anticoagulants - Levi, M.; Eerenberg, E. S.; Kampuisen, P. W. (Hämostaseologie, 2011)
Anticoagulants are effective in the prevention and treatment of a variety of arterial and venous thrombotic disorders but are associated with an increased risk of serious bleeding complications. Based on well documented studies of patients using vitamin K antagonists the incidence of major bleeding is 0.5%/year and the incidence of intracranial bleeding is 0.2%/year, however, in real life practice this incidence may be even higher. Risk factors for bleeding are the intensity of anticoagulation, the management strategy to keep the anticoagulant effect in the desired range, and patient characteristics. Recently, a new generation of anticoagulants have been developed and is currently evaluated in clinical trials. Initial results show a similar or superior efficacy over conventional anticoagulant agents with a good safety profile. In case of serious bleeding complications in a patient who uses vitamin K antagonists, this anticoagulant treatment can be quickly reversed by administration of vitamin K or coagulation factor concentrates. For the newer anticoagulants, quick reversal strategies are more cumbersome, although some interventions, including prothrombin complex concentrates, show promising results in initial experimental studies.
Keywords: Anticoagulants; vitamin K antagonists; heparin; pentasaccharide; dabigatran; rivaroxaban